2020
DOI: 10.1021/acs.est.0c00218
|View full text |Cite
|
Sign up to set email alerts
|

Fe2+/HClO Reaction Produces FeIVO2+: An Enhanced Advanced Oxidation Process

Abstract: The reaction between Fe 2+ and HClO constitutes a promising advanced oxidation process (AOP) for removing pollutants from wastewater, and • OH has been considered the dominant reactive oxidant despite limited evidence for this. Herein, we demonstrate that the Fe 2+ /HClO reaction enables the production of Fe IV O 2+ rather than • OH in acid medium, a finding that is strongly supported by multiple lines of evidence. Both X-ray absorption near-edge structure spectroscopic tests and Mossbauer spectroscopic tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(80 citation statements)
references
References 52 publications
(120 reference statements)
6
72
0
Order By: Relevance
“…However, most recently, some researchers suggested that Fe IV O 2+ could also make a significant contribution to wastewater decontamination (Liang et al 2020). Therefore, to fully identify the potential reactive species involved in the HClO/Fe 2+ process, DMSO was used as a capturing agent for  OH, and PMSO was selected to determine Fe IV O 2+ by measuring the conversion rate of PMSO to PMSO2 in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most recently, some researchers suggested that Fe IV O 2+ could also make a significant contribution to wastewater decontamination (Liang et al 2020). Therefore, to fully identify the potential reactive species involved in the HClO/Fe 2+ process, DMSO was used as a capturing agent for  OH, and PMSO was selected to determine Fe IV O 2+ by measuring the conversion rate of PMSO to PMSO2 in this work.…”
Section: Resultsmentioning
confidence: 99%
“…([Fe IV =O] 2+ , E 0 = 2.0 V/SHE), should be an important reactive species produced from the reaction between HClO and Fe 2+ (reaction 11), which was neglected by the previous studies (Liang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…88 Recently, the generation of high-valent metal species has been successfully veried in various kinds of AOPs. [89][90][91] In the Fe(II)/O 3 system, the involvement of high-valent iron-oxo species (Fe(IV)-oxo) formed from the reaction of Fe(II) with O 3 was identied by 18 O isotopelabeling technique. 92 The generated high-valent metal-oxo species are highly reactive and capable of oxidizing the organic contaminants.…”
Section: Compositing and Doping With Metalsmentioning
confidence: 99%
“…It can provide solid evidence for the generation of Fe(V)/Fe (IV) or other reactive oxidant species (ROS), and light up the way for exploring the electron transfer mechanism. Particularly, the X-ray absorption fine structure (XAFS) spectroscopy and Mössbauer spectroscopy are able to detect Fe(V)/Fe(IV) in situ, which will promote the application of spectroscopic technique in investigating the oxidation mechanism of Fe(VI) (Novak et al, 2018;Liang et al, 2020).…”
Section: Oxidizing Mechanism Of Fe(vi)mentioning
confidence: 99%
“…The in situ generated Fe(IV) can degrade the target contaminants in seconds to minutes (Mártire et al, 2002;Pestovsky and Bakac, 2004), which alleviates the negative effects of the self-decay of ferrates. Subsequently, many studies also highlighted the superiority of the in situ generated Fe(IV) species produced by Fe aq 2+ and some other oxygen-atom donors such as hypochlorous acid (Liang et al, 2020), peroxydisulfate (Wang et al, 2018b), hydrogen peroxide (Bataineh et al, 2012), and peracetic acid (Kim et al, 2019) under certain reaction conditions. The in situ generation of Fe(IV) offers an arena for promoting the abatement of contaminants, however, there are still some limitations.…”
Section: Replacement Of Fe(vi) With Fe(v)/fe(iv)mentioning
confidence: 99%